Problems with reclamation of acid lakes in the area of Muzakow lakes (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
In the paper is described actual state of environment after brown-coal exploitation with open-pit and deep-boring methods. The results of recultivation- investigations are shown, which shown the problems of the strong acid lakes- recultivation. In the paper are also shown the geological and hydrogeological characteristics of the coal deposit area.